Pengaruh Live Streaming terhadap Customer Churn pada Tiktok Shop: A Stimulus-Organism-Response Framework - Rizki Wahyuning Damayanti; Mega Handayani (Strata Business Review, 2023)
This research aims to explore how live streaming influences customer churn on TikTok Shop with arousal and pleasure being mediating variables. This research uses the Stimulus-Organism-Response (SOR) framework, the stimulus is live streaming social commerce TikTok Shop, the organism is passion and pleasure, and the response is customer churn. This research is based on the theory of social presence, where this theory identifies three dimensions of social presence in live streaming, namely the social presence of broadcasters, the social presence of viewers, and the social presence of live streaming. This research is quantitative with surveys as the data collection method. This research data collection was carried out on all Indonesian people who had made purchases while live streaming TikTok aged 18 to 40 years. This research has a sample of 129 respondents. The results of this research found that live streaming has a negative and significant effect on customer churn, and pleasure mediates the effect of live streaming on customer churn. Meanwhile, arousal was proven not to mediate the influence of live streaming on customer churn.